In-situ determination of the wall's thermal properties for energy retrofit in a colonial heritage building: the Cabildo of Salta, Argentina - Flores Larsen, Silvana Elinor (2021)
The energy retrofit of historic buildings requires identifying the materials and thermal properties of the building fabric. This information is essential for building energy simulation, conservation, and restoration, but, unfortunately, it is usually scarce or even non-existent in documentary sources or historical studies. This paper presents the non-destructive thermal characterization of the façade walls of the historic Cabildo of Salta, Argentina. The interdisciplinary methodology includes preliminary historical and morphological studies, identification of the masonry patterns through infrared thermography, characterization of the material thermal properties through non-destructive measurements and novel dynamical computational methods, and the integrated analysis of the results based on a cross-referencing of masonry pattern, materials, and historical data. The obtained results provide scientific support for decision making in future energy retrofit strategies and building restoration.